Effects of exercise prescription on blood lipid profiles, health related fitness component and anthropometric profile of subjects with high cholesterol level - Ismail, Mohamed Saat (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2010)
The aim of this study was to compare the effectiveness of exercise prescription on lipid profile changes, cardiorespiratory fitness, blood pressure, resting heart rate, musculoskeletal fitness and anthropometry measurement of high cholesterol subject. Nine untrained male subjects age between 40 to 55 year and were serum total cholesterol level more than 5.8 mmol.l-1 randomized assigned between three days per week (Group 1, n=3), six days per week (Group 2, n=3) at 50% V02rnax for 60 minutes throughout twelve weeks or no exercise (Control group, n=3) . Their fasting blood lipid will be assessed for both groups one day before intervention programme (pre), after four weeks of intervention programme (post-1), after eight weeks of intervention programme (post-2) and after twelve weeks of intervention programme (post-3) to compare the changes of blood lipid profiles. After twelve weeks intervention programme it showed greater positive improvement of exercise with a reduction in 17.1% triglycerides, and 15.4% VLDL in Group 2. Meanwhile positive improvement also was seen with a reduction in 9.0% total cholesterol, 11.5% LDL cholesterol in Group 1. Additionally, both groups showed slightly improvement in HDL cholesterol. Therefore, both exercise prescription was sufficient to alter overall lipid profile changes including HDL cholesterol and reduces cardiovascular risk in previously high cholesterol subjects. But it is encourage increasing sample size and prolonged duration more than twelve weeks for additional benefit. The blood pressure (BP), resting heart rate (RHR) and health related fitness test consisted of maximum oxygen consumption (V02max), back strength (BS), leg strength (LS), dominant hand grip strength (HG), sit up (SU), push up (PU) and sit and reach (SR) were performed at a day before intervention programme (pre), at the end of week 4 (post-1) and week 8 (post-2). After eight weeks exercise intervention programme, Group 1 demonstrated greater improvement with decreased in systolic BP (2.7%), diastolic BP (6.2%) and RHR (9.0%) compared to Group 2. While Group 2 showed better improvement in V02max (4.9%), (BS (26.1%), LS (35.2%), HG (3.6%), PU (46.0%) and SR (3.9%) compared to Group 1. These findings suggested that low frequency exercise group (3 times/week) induced more positive changes in resting heart rate and blood pressure. While, high frequency exercise group (6 times/week) induced more positive changes in V02max. muscular strength, push-up and sit and reach. In order to maximize the effects of moderate intensity exercise of 60 min/session on cardiorespiratory fitness (V02max). high frequency exercise of 3 times per week should be recommended. The anthropometric measurements were performed at a day before intervention programme (pre), at the end of week 4 (post-1) and week 8 (post-2). After 8-week exercise intervention programme, group 2 showed greater improvements with decreased in body weight (2.6%), BMI (2.4%), reduced in subscapular (10.4%) and front thigh (13.1%) skinfold thickness, and decreased in girth of arm relaxed (1.3%), arm flexed (1.3%), waist (1.3%), hip (1.6%) and calf (4.1%) than group 1. While group 1 show more improvements that decreased in triceps (7.8%), biceps (5.9%), iliac crest (8.6%), medial calf (3.4%), and calf girth (0.3%) than group 2. These findings suggest that high frequency exercise group (6 dlwk) had greater reduction in anthropometric measurements more than low frequency exercise group (3 dlwk). In order to maximize the effects of moderate intensity exercise of 60 min/session on anthropometric measurements, high frequency exercise of 6 times per week should be recommended